2014
DOI: 10.1136/postgradmedj-2013-131994
|View full text |Cite
|
Sign up to set email alerts
|

Hidradenitis suppurativa: a common and burdensome, yet under-recognised, inflammatory skin disease

Abstract: Hidradenitis suppurativa (HS) is a chronic, relapsing, inflammatory skin condition that typically occurs after puberty. The primary clinical presentation is painful inflamed nodules or boils in the apocrine gland-bearing regions (armpits, genital area, groin, breasts and buttocks/anus) that progress to abscesses, sinus tracts and scarring. Severity is typically described according to three Hurley categories, with most patients having mild or moderate disease. Estimated prevalence is 1–4% worldwide and HS is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
129
0
29

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(160 citation statements)
references
References 44 publications
2
129
0
29
Order By: Relevance
“…HS is a chronic inflammatory debilitating skin disease and is one of the most distressing conditions observed in dermatology [14][15][16]. Nevertheless, patients experience a significant delay in diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…HS is a chronic inflammatory debilitating skin disease and is one of the most distressing conditions observed in dermatology [14][15][16]. Nevertheless, patients experience a significant delay in diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…HS affects young adults, with disease onset typically between the second and fourth decades of life [6,7]. Within the adult European population, a prevalence of 1% has been reported [8], although true prevalence is likely to be higher due to problems of under-recognition [9,10]. Whilst there are no published data on HS prevalence in the UK, it has been suggested that this might be in the region of 1 in 600 [6].…”
Section: The Decision Problemmentioning
confidence: 99%
“…HS has a higher prevalence in women than men and around one-third of patients have the disease in first-degree relatives. The other important known risk factors for HS are obesity and cigarette smoking [8][9][10]. Studies have suggested that active disease can substantially impair patients' health-related quality of life (HRQoL), with an impact which exceeds that of other skin diseases such as alopecia, acne, mild to moderate psoriasis, vascular anomalies of the face and atopic dermatitis.…”
Section: The Decision Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Такие проявления болезни, как выраженная боль, ограничение подвижности, сви-щевые ходы с отделяемым, имеющим неприятный запах, приводят к снижению самооценки, работоспособности, развитию депрессии и, как следствие, социальной изоля-ции больных [21][22][23].…”
unclassified